Answer:
x=5,y=1 and z=-2
Explanation:
We are given that system of equation
(I equation)
(II equation )
(III equation )
Equation II multiply by 3 then add with equation I
Then, we get
....(Equation IV)
Subtract equation II from equation III then we get
(equation V)
Adding equation IV and equation V then, we get
![9x=45](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yxcrwjkcvbueksfzd8gmhzz5972s6vwgzy.png)
Substitute x=5 in equation V then, we get
![2(5)-6y=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/m3tygbsw9wdmiu0wfer9s5ywq2wdvlj2cu.png)
![10-6y=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1p95q9wxh3csx62sxp5d4fgsgwwuo6fyow.png)
![6y=10-4=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/afmo5x366rav7m9vikmg3o0xvect2tayz2.png)
![y=1](https://img.qammunity.org/2020/formulas/mathematics/high-school/shmuyul9qjj9r1nqzr15kdsrv22lgw6ocn.png)
Substitute x=5 and y=1 in equation then, we get
![5-3(1)+3z=-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/suionqodm3fck0svdm3lx2th598ep58yqt.png)
![2+3z=-4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f8ia4n9vx02q6pvou5bajlsedp8srv7xyi.png)
![3z=-4-2=-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lwvfxeo3b6dv1wlx9chebk7sc7cq3tty6c.png)
![z=(-6)/(3)=-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9mt6e7mr5iwxutvbnnqxy69n39any8xkh0.png)
Hence, the solution for the given system of equation is given by
x=5,y=1 and z=-2